Anti-inflammatory role of Prunus persica L. Batsch methanol extract on lipopolysaccharide-stimulated glial cells - Seo, Kyoung Hee (Mol Med Rep, 2020)
Glial cells are the resident immune cells of the central nervous system. Reactive glial cells release inflammatory mediators that induce neurotoxicity or aggravate neurodegeneration. Regulation of glial activation is crucial for the initiation and progression of neuropathological conditions. Constituents of the peach tree (Prunus persica L. Batsch), which has a global distribution, have been found to exert therapeutic effects in pathological conditions, such as rashes, eczema and allergies. However, the therapeutic potential of its aerial parts (leaves, fruits and twigs) remains to be elucidated. The present study aimed to evaluate the anti-inflammatory role of P. persica methanol extract (PPB) on lipopolysaccharide (LPS)-stimulated glial cells. High-performance liquid chromatography coupled with tandem mass spectrometry analysis showed that PPB contained chlorogenic acid and catechin, which have antioxidant properties. Western blot and reverse transcription polymerase chain reaction results indicated that PPB reduced the transcription of various proinflammatory enzymes (nitric oxide synthase and cyclooxygenase-2) and cytokines [tumor necrosis factor-α, interleukin (IL)-1β and IL-6] in LPS-stimulated BV2 cells. In addition, PPB inhibited the activation of NF-κB and various mitogen-activated protein kinases required for proinflammatory mediator transcription. Finally, nitrite measurement and immunocytochemistry results indicated that PPB also suppressed nitrite production and NF-κB translocation in LPS-stimulated primary astrocytes. Thus, PPB may be used as a potential therapeutic agent for neurodegenerative diseases and neurotoxicity via the suppression of glial cell activation.